Hubungan harga saham CPO dengan nilai tukar IDR selama fluktuasi inflasi - Septiana, Febby; Daniella, Alditha Cristhmas Putri (Riset Akuntansi dan Manajemen Pragmatis, 2023)
Several macroeconomic indicators in Indonesia, such as inflation and the exchange rate, tend to be more controlled from the end of 2022 to early 2023. However, during this period the price of CPO shares on the capital market tends to be more fluctuate. This study aims to examine the correlation of CPO share prices with exchange rates during inflation fluctuations, especially from 1 December 2022 to 30 April 2023. This study finds that the highest and most stable market price of CPO shares was in February 2023. The finding also indicates that the price movement pattern CPO stock market is inconsistent with changes in the rate of inflation. Apart from that, the finding also shows a tendency for a moderate relationship between the market price of CPO shares and the exchange rate. Another implication is that the increase in the exchange rate (depreciation of the IDR over USD) will be accompanied by a decrease in the market price of CPO shares.